Analysis of The Influence of Motivation, Environment, and Work Stress on Employee Performance Through Job Satisfaction As Intervening Variable (Case Study Of PT. XYZ) - Yanuar, Kukuh Eska; Suparto, Suparto (Jurnal SENOPATI : Sustainability, Ergonomics, Optimization, and Application of Industrial Engineering, 2020)
PT. XYZ is a company engaged in construction specifically steel fabrication. The problem encountered by company was frequent overtimes with low remuneration but cannot meet production target. The objective of study was to know the influence of motivation, environment,stress on employee performance through job satisfaction as intervening variable. The method used was Structural Equation Modeling with IBS SPSS AMOS software. The results of study indicated that motivation had positive influence of 0.229, environment had positive influence of 2.746, and stress had significant influence of 0.139 on job satisfaction. Motivation had positive influence of 0.910, environment had positive influence of 2.526, and stress had negative influence of -0.221 on employee performance. Motivation had positive influence of 0.093, environment had positive influence of 1.120, and stress had positive and significant influence of 0.056 on employee performance through job satisfaction as intervening variable. Job satisfaction had positive influence of 0.408 on employee performance.Keywords: motivation, environment, stress, structural, equation, modeling